Effectiveness of Passport Application’s Queuing Flow In Order to Improve Public Services - Case Study of APAPO Implementation at the Immigration Office Class I Special Non Border Control South Jakarta - Beauty Maharani Matutina (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2019)
Public services in Indonesia have an important role in every aspect such as economic, social and political. In addition, services like this are also an important element in improving the quality of social life in social life. High quality services are one of the main concerns among the social community, therefore it needs to be considered in providing services. The use of information technology in passport services truly helps increasing the work’s effectiveness and efficiency, which is the service in applying for a passport at the immigration office. Therefore, it is necessary for public service providers to pay attention in carrying out activities to fulfill society’s demands.